Therapeutic Implementation of a Custom Dynamic Elbow Brace for Children With Neonatal Brachial Plexus Palsy: A Case Report. Issue 1 (January 2021) - Torrey, Michelle
Abstract : Purpose: The objective of this analysis is to present the benefits and functional outcomes when using a custom dynamic elbow brace as an adjunct to therapeutic interventions for a child with neonatal brachial plexus palsy. Summary of Key Points: Impairments associated with neonatal brachial plexus palsy can cause lifelong limitations of mobility, dexterity, and functional use of the involved upper extremity. The functional design of the custom dynamic elbow brace provided therapeutic versatility including immobilization, active-assisted controlled movement, and resistance exercise. These features facilitated efficient and functional muscle activation patterns, negating compensatory or substitute movements. Conclusions and Recommendations for Clinical Practice: The brace provided opportunities for focused muscle activation and subsequent improvements in strength, development of motor control, and functional mobility. Using a custom dynamic elbow brace was an effective therapeutic tool, used in conjunction with a comprehensive treatment program, and contributed to a successful outcome. Abstract : The objective of this analysis is to present the benefits and functional outcomes when using a custom dynamic elbow brace as an adjunct to therapeutic interventions for a child with neonatal brachial plexus palsy.